Relasi Sistem Tanda Verbal dan Tanda Visual pada Iklan Rokok di Youtube - Paul Diman; Albertus Purwaka; Ina Nurensia Maleyati (SUAR BETANG, 2020)
This study discusses the relationship between verbal and visual signs system in cigarette advertisements in Youtube. The purpose of this study is to describe how the visual and verbal signs system are the basic elements of message formation and the meaning relations of connotations that appear in cigarette advertisements in Youtube. This becomes interesting due to the prohibition against showing examples of cigarette products themselves in the mass media. Cigarette advertisements show their own uniqueness, namely that they always show the male figure in their advertisements with various kinds of activities they do. The method used in this research is descriptive qualitative method with data analysis techniques using Charles Sanders Peirce's semiotic analysis. The data in this study were obtained from downloaded video advertisements in Youtube in the form of six cigarette advertising videos, then playing the video into pieces of images, all of which would be analyzed. The writer the analyze the relationship between the verbal sign system and visual signs, in the form of images and writings on cigarette advertisements on Youtube with the meanings contained therein and provide interpretations of the connotative meaning of the interaction of verb signs and visual signs. Based on the analysis, there are verbal and visual signs that have their own meanings, which try to communicate their message through these signs. Verbal signs in cigarette advertisements on Youtube can be found in the tagline, which contains the meaning that appears in the visual sign of the ad. In this case, verbal signs are an important element in adapting the advertising language used to foster reminders and brand awareness of these cigarette products. Visually, cigarette advertisements on Youtube show the independence of these men, indicating the independent nature of men who are able to solve all their problems alone. The construction of the visualization of the male figure in this advertisement also displays a positive image, namely the loving nature of pets. The ability of men to be able to manipulate is also a new image in the male image.  AbstrakIklan merupakan bentuk komunikasi nonpersonal yang menjual pesan-pesan secara persuasif dari sponsor. Iklan-iklan rokok yang tayang di youtube selalu unik dan menarik untuk disimak. Hal ini disebabkan oleh adanya larangan untuk menampilkan contoh produk rokok itu sendiri. Untuk tetap bisa beriklan, agency periklanan melakukan strategi dengan menciptakan iklan rokok kreatif.salah satunya dengan menggunakan komunikasi tanda verbal dan tanda visual, yang beroperasi pada dua jenjang, yaitu tanda secara individual dan tanda sebagai sebuah kelompok atau kombinasi. Tujuan utama penelitian ini adalah melakukan deskripsi, eksplanasi, dan kajian terhadap sistem tanda verbal dan tanda visual serta relasi makna yang terkandung pada  iklan rokok yang ada di youtube. Penelitian ini menggunakan metode deskriptif dengan analisis semiotika komunikasi. Hasil dari analisis mengungkapkan bahwa relasi system tanda visual memunculkan adanya deskripsi berkenaan Relasi sistem tanda verbal dan tanda visual pada iklan rokok U mild memberikan ruang yang cukup luas untuk dipersepsikan dan pesan yang disampaikan. Sebagian besar iklan rokok U mild mengarah pada konstruksi maskulinitas yang dapat dilihat pada penggambaran berbagai aspek seperti segi fisik, ekonomi, sifat, dan aktivitas.. maskulinitas juga sering menampilkan karakter laki-laki yang sukses dan hidup di kalangan kaum menengah keatas. Hal ini dikarenakan kesuksesan juga merupakan salah satu ciri maskulinitas sehingga penggambaran kesuksesan ini mengokohkan konsep maskulinitas yang ada. Konstruksi maskulinitas dalam iklan ini menampilkan juga laki-laki yang penyayang dan mampu melakukan manipulasi.